Optimal PID controller design for AVR system using particle swarm optimization algorithm - Rahimian, Mohammad Sadegh; Raahemifar, Kaamran (2011 24th Canadian Conference on Electrical and Computer Engineering(CCECE), 2011)
A proportional-integral-derivative (PID) controller is a generic feedback controller widely used in industrial control systems, process control, motor drive, and instrumentation. Despite the popularity, the tuning aspect of PID coefficients is a challenge for researchers and plant operators. In this paper Particle Swarm Optimization Algorithm is used to design the optimum PID controller parameters for a high order automatic voltage regulator (AVR). The proposed approach with new defined time-domain cost function, has a very easy implementation, stable convergence characteristic and ability of fast tuning of optimum PID controller parameters that requires fewer number of iterations. In order to evaluate the performance of the PSO-PID controller, the results are compared with the genetic algorithm (GA). The comparison shows the PSO-PID algorithm has more efficiency and robustness in improving the step response of an AVR system.